POLYMORPHISM ASSOCIATED XRCC1 GENE WITH LATE TOXICITY AFTER RADIATION THERAPY IN BREAST CANCER PATIENTS IN IRAQ - Nawres Adnan Abdulameer (Chelonian Research Foundation, 2023)
Risk of normal tissue toxicity restricts the radiation dosage that can be safely administered in radiotherapy. All of the studies confirmed that the rs2682585 mutation of the XRCC1 base excision repair gene is associated with late radiation damage in normal tissues. Carrying the rare allele was linked to a considerably decreased incidence of skin toxicities in the combined analysis of discovery and replication cohorts. With the help of a staged design with replication, we found a variant allele in the XRCC1 base excision repair gene that, when combined with other variants, may be utilised to predict late toxicities after radiation in breast cancer patients. Key words: XRCC1, breast cancer, radiation therapy